2019
DOI: 10.1186/s12887-019-1787-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-component school-based program on body mass index, cardiovascular and diabetes risks in a multi-ethnic study

Abstract: BackgroundMexico occupies one of the first places worldwide in childhood obesity. Its Mestizo and Indigenous communities present different levels of westernization which have triggered different epidemiological diseases. We assessed the effects of a multi-component school-based intervention program on obesity, cardiovascular and diabetes risk factors.MethodsA physical activity, health education and parent involvement (PAHEPI) program was developed and applied in six urban (Mestizo ethnic group) and indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…All children were recruited by the Por tu Salud Project, with the goal of researching genetic and environmental factors of childhood obesity [22]. As inclusion criteria, we selected children of both sexes, with obesity, overweight and normal weight, who attended the schools.…”
Section: Methodsmentioning
confidence: 99%
“…All children were recruited by the Por tu Salud Project, with the goal of researching genetic and environmental factors of childhood obesity [22]. As inclusion criteria, we selected children of both sexes, with obesity, overweight and normal weight, who attended the schools.…”
Section: Methodsmentioning
confidence: 99%
“…Aerobic and strength exercises are effective in reducing overweight, which is the major cause of MetS, in children and adolescents who are obese 25,26 . To prevent MetS among adolescents at school, physical activity should be increased, and more special management is needed, especially for adolescents who are obese and do not exercise 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (26; 89.6%) included a nutritional component, 19 (65.5%) a PA component, 12 (41.0%) a behavioural or psychological component, and only six (20.7%) included environmental changes to support obesity prevention and lifestyles improvement. Only three studies (10.3%; Costa-Urrutia et al, 2019;Safdie et al, 2013a, b;Levy et al, 2012a, b) included several components. However, only one (Safdie et al, 2013a(Safdie et al, , 2013b was implemented for over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the studies' funding, nine (31.0%) did not report any funding, and only one (Arroyo et al, 2018) reported not receiving any funding for the study. Three studies (10.3%, Gatica-Dominguez et al, 2019;Perichart-Perera et al, 2008;Polo-Oteyza et al, 2017) reported receiving funding from the food industry, three more (10.3%; Costa-Urrutia et al, 2019;Ramirez-Lopez et al, 2005;Levy et al, 2012a, b) reported using funds from local authorities. Five studies (17.2%; Mejia et al, 2016;Padilla-Raygoza et al, 2013;Rodriguez-Ventura et al, 2018;Salazar-Vazquez et al, 2016;Zacarias et al, 2019) reported using public national funding, and five more (Alvirde-Garcia et al, 2013;Bacardi-Gascon & Jiménez-Cruz 2012;Benitez-Guerrero et al, 2016;Martinez-Andrade et al, 2014;Vilchis-Gil et al, 2016) received funding from public institutions (e.g., public hospitals or public universities).…”
Section: Quality and Risk Of Bias Appraisalmentioning
confidence: 99%